2015
DOI: 10.1121/1.4916592
|View full text |Cite
|
Sign up to set email alerts
|

Human middle-ear model with compound eardrum and airway branching in mastoid air cells

Abstract: An acoustical/mechanical model of normal adult human middle-ear function is described for forward and reverse transmission. The eardrum model included one component bound along the manubrium and another bound by the tympanic cleft. Eardrum components were coupled by a time-delayed impedance. The acoustics of the middle-ear cleft was represented by an acoustical transmission-line model for the tympanic cavity, aditus, antrum, and mastoid air cell system with variable amounts of excess viscothermal loss. Model p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
(144 reference statements)
1
7
0
Order By: Relevance
“…They concluded that the similarity of SFOAE and DPOAE at high response frequencies suggests that middle-ear function limits reverse propagation of the evoked OAE back to the ear-canal microphone. This spectral pattern was similar to a model prediction (Keefe, 2015) of the reverse middle-ear pressure reflectance magnitude. This model was developed based on human temporal-bone measurements up to 8 kHz (Nakajima et al, 2008; Puria, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…They concluded that the similarity of SFOAE and DPOAE at high response frequencies suggests that middle-ear function limits reverse propagation of the evoked OAE back to the ear-canal microphone. This spectral pattern was similar to a model prediction (Keefe, 2015) of the reverse middle-ear pressure reflectance magnitude. This model was developed based on human temporal-bone measurements up to 8 kHz (Nakajima et al, 2008; Puria, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…The main function of this ossicular assembly is to mediate the transmission of vibrations from the tympanic membrane through the handle of malleus ( Manubrium mallei ) and send them over towards the components of the internal ear, acting as a transformer of impedance of the air acoustic energy towards the fluids of the inner ear (Wilson, 1987),(Keefe, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The network topology of the human ear impedance model is illustrated in the equivalent circuit model in Figure 4, which is combined with reports by different investigators, 22,28,29 and used to study the role of the third windows during the forward and reverse stimulations. 24 Briefly, the ear canal is modeled as a lossy cylindrical tube with a length of 2 × 10 −2 m and a cross-sectional area of 4.3 × 10 −5 m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The parameters of each component are listed in Table 1.Three transformers (tympanic membrane area A TM = 6 × 10 −5 m 2 , ossicular lever ratio of middle ear N ME = 1.3, and the stapes footplate area A SF = 3.14 × 10 −6 m 2 ) are arranged in the middle ear to obtain the pressure gain and impedance matching of the middle ear. 28,29 The outer ear and the middle ear correspond to the middle-ear impedance Z ME in Figure 3 during reverse stimulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation